History of Labor in the United States - Cross, Ira B.; Commons, John R.; Saposs, David J.; Sumner, Helen L.; Mittelman, E. B.; Hoagland, H. E.; Andrews, Julia B.; Andrews, John B.; Perlman, Selig (Quarterly Journal of Economics, 1918)
Journal Article History of Labor in the United States Get access Ira B. Cross Ira B. Cross University of California Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 32, Issue 4, August 1918, Pages 667–673, https://doi.org/10.2307/1883793 Published: 01 August 1918